MO657RANDOMIZED CONTROL TRIAL OF INTERMITTENT HEMODIALYSIS WITH REGIONAL CITRATE VS PRIMING HEPARIN WITH PREDILUTION IN PATIENTS AT RISK OF BLEEDING. (29th May 2021) - Moranne, Olivier; Cariou, Sylvain; Messikh, Ziyad; Pambrun, Emilie; Garo, Florian; Schultz, Celine; Prouvot, Julien; Renaud, Sophie; Reboul, Pascal
Abstract: Background and Aims: Standard intermittent haemodialysis (SIHD) includes anticoagulation to avoid clotting of the dialysis system. In patients at high risk for bleeding, alternativ methods have been developed to avoid systemic anticoagulation. Regional citrate anticoagulation (RCA) is usually used with continuous renal replacement therapy and low blood flow but the Promotheus® device (Freseinus Medical care-Germany) allow RCA for liver support therapy with dialysis system 4008H® and blood flow over 200ml/min. The aim of this study was to compare the IHD with RCA (IHD-RCA) to SIHD without systemic anticoagulation in patients at high risk for bleeding. Method: We conducted a randomized control trial study evaluating the superiority of IHD-RCA with Prometheus® device compared to SIHD with 5008H® dialysis monitor using priming heparin (5000UI unfractionated heparin) with predilution (25 ml/min) in a 4 hour IHD strategy in patients with high risk for bleeding. Randomization was stratified on vascular access. Sixty adult patients were randomly allocated to one IHD-RCA session or SIHD in a one ICU unit university center from 2019 to 2020. Bleeding risk was defined by nephrologist and inclusion need well-functioning fistula or double-lumen catheters with a protocol blood flow higher than 200 ml/min. The primary end point was the percentage of successful study period, defined as no premature interruption of a 4 hour hemodialysis session. Secondary end points included dialysis adequacy (KT/V), dialysis circuit bubble trap status and dialyzer membrane status by visual inspection. The study was declared in ClinicalTrial NCT03562754. Results: Two patients from IHD-RCA were excluded of analysis because of early vascular access failure. Causes of bleeding risk were activ bleeding in 25(43%), recent surgery or organ biopsy in 31(53%) and Stroke in 2 sessions. 10(17%) patients were treated by IHD for AKI3 and other for chronic hemodialysis. 24(41%) patients have fistula, and the mean blood flow was significantly higher in SIDH group vs IHD-RCA (294 vs 263 ml/min, p<0.001). All sessions were performed with FX800 dialyzer (Polysulfone, hollow-filter 1.8M2, FMC). No statistically significant difference was observed for primary end point between group with 96% (27/28) of success for IHD-RCA and 83% (23/28) for SIHD (p=0.09). For secondary end point, no statistically significant difference was observed for KT/V delivery between group (1.69 vs 1.61, p=0.27) but score was statistically significant different between groups for visual inspection of fiber bundles (p<0.01) and dialysis circuit bubble traps aspect ( p<0.01 ) with higher score for SIHD. Conclusion: No statitically significant difference was observed between 2 groups for 4-hour heparin-free hemodialysis sessions but we observed lower session failure with IHD-RCA. We confirm efficacy of Prometheus device for IHD-RCA in this population. Moreover, we report a low risk of 4-hour heparin-free session failure with SIHD without systemic anticoagulation using double lumen access, priming heparin, high blood flow, predilution and Polysulfone High-flux dialyser in comparison with other studies.